2013
DOI: 10.3109/03639045.2013.873448
|View full text |Cite
|
Sign up to set email alerts
|

Development ofPasteurella multocida-loaded microparticles for hemorrhagic septicemia vaccine

Abstract: In this study, Pasteurella multocida-loaded alginate microparticles (MPs) for subcutaneous vaccination was developed by emulsification-cross-linking technique. Formulation parameter was varied as a ratio of polymer and bacterin. Optical microscopy revealed spherical particles with uniformly distribution. A mean particle size of approximately 6 µm has been successfully constructed using simple mixer and ultrasonic probe. The zeta potential of the MPs showed negatively charge of approximately -23 mV determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The Tiyaboonchai lab encapsulated Pasteurella multocida within alginate microparticles for subcutaneous injections. Key to this study was a 6‐month storage test, where antigenicity was investigated in samples kept either at 4 or 37 °C (Nimtrakul et al, 2015). Results revealed that mice injected with either formulation elicited an immune response similar to freshly encapsulated antigens.…”
Section: The Interaction Between Antigen and Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tiyaboonchai lab encapsulated Pasteurella multocida within alginate microparticles for subcutaneous injections. Key to this study was a 6‐month storage test, where antigenicity was investigated in samples kept either at 4 or 37 °C (Nimtrakul et al, 2015). Results revealed that mice injected with either formulation elicited an immune response similar to freshly encapsulated antigens.…”
Section: The Interaction Between Antigen and Biomaterialsmentioning
confidence: 99%
“…Encapsulation infiltration have been more heavily investigated owing to the potential stability they the antigens trapped within. Created with BioRender.com samples kept either at 4 or 37 C (Nimtrakul et al, 2015). Results revealed that mice injected with either formulation elicited an immune response similar to freshly encapsulated antigens.…”
Section: Antigenicity and Long-term Stabilitymentioning
confidence: 99%
“…In vitro assays have been performed using macrophages and aortic endothelial cells [348][349][350][351]. Mouse models can play an important role in investigation of pathogenesis and vaccine development [317,[351][352][353][354][355][356][357][358][359][360][361][362][363]. Rats with or without immunosuppression have also been used to explore pathogenesis and novel vaccines [349][350][351][364][365][366].…”
Section: Hemorrhagic Septicemiamentioning
confidence: 99%